Risk Analysis in The Business Process Management And Recording Electricity Costs (Case Study in an Oil and Gas Company in Indonesia) - Febriandaru Kurniasih; Agustinus Nicholas L. Tobing (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research was conducted onone of the State-Owned Enterprises (BUMN) that is engaged in the oil and gas sector which has a trend of outstanding electricity costs that continue to increase from year to year. This study aims to analyze the factors that cause outstanding transactions for recording electricity costs, the risks that arise and corrective actions that must be taken by the company management. The research was conducted by collecting company internal data and semi-structured interviews with informants before and after the company implemented Shared Services. The research method uses qualitative methods with an exploratory case study approach. Based on the results of the study, there are seven risks, namely understated expense, over budget, over payment, company losses, abnormal balance of account payables (debit balance), inaccurate recording, and declining company reputation. The results showed that the risk decreased after risk mitigation was carried out using the Shared Services business model and Robotic Process Automation (RPA) technology. The author suggests that Company should implements a roadmap in business processes, and consistently manages the business process of recording electricity costs in accordance with established policies and procedures.